2005
DOI: 10.1172/jci23237
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic AKAP9-BRAF fusion is a novel mechanism of MAPK pathway activation in thyroid cancer

Abstract: Genes crucial for cancer development can be mutated via various mechanisms, which may reflect the nature of the mutagen. In thyroid papillary carcinomas, mutations of genes coding for effectors along the MAPK pathway are central for transformation. BRAF point mutation is most common in sporadic tumors. By contrast, radiation-induced tumors are associated with paracentric inversions activating the receptor tyrosine kinases RET and NTRK1. We report here a rearrangement of BRAF via paracentric inversion of chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(171 citation statements)
references
References 43 publications
6
159
1
5
Order By: Relevance
“…BRAF fusions have also been described in postChernobyl thyroid cancer, suggesting that this is a new mechanism of BRAF activation in human cancers (Ciampi et al 2005, Ricarte-Filho et al 2013. As far as we known, AGK-BRAF fusion was described in a tumor from one radiation-exposed PTC case who was 13 years old at surgery (Ricarte-Filho et al 2013), while AKAP9-BRAF was identified in three tumors from radiation-exposed patients.…”
Section: Other Fusions Transcriptsmentioning
confidence: 85%
See 1 more Smart Citation
“…BRAF fusions have also been described in postChernobyl thyroid cancer, suggesting that this is a new mechanism of BRAF activation in human cancers (Ciampi et al 2005, Ricarte-Filho et al 2013. As far as we known, AGK-BRAF fusion was described in a tumor from one radiation-exposed PTC case who was 13 years old at surgery (Ricarte-Filho et al 2013), while AKAP9-BRAF was identified in three tumors from radiation-exposed patients.…”
Section: Other Fusions Transcriptsmentioning
confidence: 85%
“…The overall prevalence of these other fusion transcripts was 6% in a pediatric radiation-exposed PTC range from 3% to 19% (Ciampi et al 2005, Sassolas et al 2012, Ricarte-Filho et al 2013 and 0% in sporadic (Ricarte-Filho et al 2013).…”
Section: Other Fusions Transcriptsmentioning
confidence: 94%
“…BRAF is a serine-threonine kinase which, upon activation by RAS , activates MEK and leads to activation of downstream effectors of the MAPK pathway. In nearly all cases (98-99% of cases) activating point mutations of BRAF involve codon 600 and result in the V600E mutation, and in 1-2% of cases other BRAF mutations such as the K601E mutation, small in-frame insertions or deletions, or BRAF rearrangement can occur (Soares et al 2003; Ciampi, et al 2005; Ciampi and Nikiforov 2005; Hou, et al 2007b; Chiosea, et al 2009). …”
Section: Molecular Genetics Of Thyroid Cancermentioning
confidence: 99%
“…Fusion of BRAF with A kinase anchor protein 9 ( AKAP9 ) is a rearrangement rarely found in sporadic thyroid cancer, although it also occurs at higher frequencies (up to 11%) in patients with a history of radiation exposure (Ciampi et al 2005). NTRK1 is a receptor tyrosine kinase and when rearranged with one of 3 potential fusion partners, activates MAPK pathway signaling (Bongarzone, et al 1998; Musholt, et al 2000).…”
Section: Emerging Novel Molecular Markersmentioning
confidence: 99%
“…Nearly all the thyroid cancers that have been attributed to external or internal radiation have been papillary in type; where the oncogenes involved have been studied rearrangements in RET rather than point mutations in BRAF have been linked to radiation carcinogenesis [24,25]. Interestingly, a rare finding in short latency papillary carcinomas in children exposed to Chernobyl fallout is activation of BRAF by rearrangement [26]. …”
Section: Molecular Findings In Sporadic and Radiation-induced Thyroidmentioning
confidence: 99%